Pengaruh Kompetensi, Kemampuan Kerja, Dan Work From Home Terhadap Kinerja Di Masa Pandemi Covid-19 - Luchia Jenifer Chircia Bana; I Gusti Dewi Adnyani (STIE Mandala Jember, 2023)
The purpose of this study was to analyze the impact of competence, work ability and work from home carried out at Santo Yoseph Junior High School Denpasar. This research was conducted using a saturated sample of 49 people who are employees and teachers. Data was collected by interview method and distributing questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that competence has a significant positive effect on performance, work ability has a positive and significant effect on performance and work from home has a negative and significant effect on performance. The theoretical implications of this study provide evidence on the development of work results or work performance carried out by teachers, especially regarding competence, work ability and work from home which are able to prove empirically the theory used in this study refers to attribution theory which is a theory that assumes that the process by which determine the causes or motives of a person's behavior. This research can be used as a reference for all parties, both for students or universities in conducting research with similar variables and for agencies in improving performance.